Translation, Transcultural Adaptation, and Validation of the Brazilian Portuguese Version of the Body Image Disturbance Questionnaire for Scoliosis (BR-BIDQ-S) - Matos, Marcos Almeida; Freitas, Maria Clara; Fernandes, Rony Britto; Oliveira, Luís Fernando Weber de; Meves, Robert (Revista Brasileira de Ortopedia, 2024)
Objective The Body Image Disturbance Questionnaire for Scoliosis (BIDQ-S) for scoliosis derives from the Body Image Disturbance Questionnaire (BIDQ) with specific adaptation for scoliosis patients. Despite its significance and applicability, this instrument has never been translated into Brazilian Portuguese. The current study aimed to translate, transculturally adapt, and validate the BIDQ-S into Brazilian Portuguese.Methods BIDQ-S was translated and culturally adapted into Brazilian Portuguese using the American Association of Orthopedic Surgeons (AAOS) criteria. The questionnaire validation relied on internal consistency and comparison with the Cobb angle, Pediatric Quality of Life Inventory (PedsQL), and Scoliosis Research Society (SRS-22). The Brazilian version (BR-)BIDQ-S validation occurred in a sample of 35 adolescents with scoliosis waiting for specialized treatment.Results Internal consistency of the BR-BIDQ-S was 0.899 according to the Cronbach's index (i.e., virtually perfect). Although BR-BIDQ-S did not correlate with the Cobb angle, it presented correlations with the Physical, Emotional, and Social domains from the PedsQL and the Function/Activity domain from the SRS-22.Conclusion BR-BIDQ-S was reliable in evaluating the body image of adolescents with scoliosis, presenting an internal consistency of 0,899 (virtually perfect). Moreover, similar to the original instrument, it correlated with PedsQL and SRS-22.
Keywords: scoliosis; evaluation; diagnosis; quality of life